Advanced Statistical Forecasting for Public Sector Financial Transformation: A Case Study of Abu Dhabi Ports - Srinivasarao Challagundla, (Journal of Computational Analysis and Applications (JoCAAA), 2026)
The contemporary public sector financial management landscape necessitates sophisticated analyticalframeworks to support strategic decision-making amid economic uncertainty. Abu Dhabi Ports Companyexemplifies the successful implementation of advanced statistical forecasting methodologies within enterprise performance management systems